2021
DOI: 10.1186/s13287-020-02074-y
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned media from endothelial progenitor cells cultured in simulated microgravity promote angiogenesis and bone fracture healing

Abstract: Background Paracrine signaling from endothelial progenitor cells (EPCs) is beneficial for angiogenesis and thus promotes tissue regeneration. Microgravity (MG) environment is found to facilitate the functional potentials of various stem or progenitor cells. The present study aimed to elucidate the effects of MG on pro-angiogenic properties and fracture repair capacities of conditioned media (CM) from EPCs. Methods Human peripheral blood-derived EPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Considering that DFO compromised the angiogenic activity of EPCs, we then examined whether four-day DFO treatment altered the expression of angiogenic proteins such as vascular endothelial growth factor (VEGF), Fms-related receptor tyrosine kinase 1 (Flt-1), kinase insert domain receptor (KDR) and TEK receptor tyrosine kinase (TIE2) in EPCs ( Figure 3C – 3F ). DFO strongly downregulated VEGF, the major angiogenic factor in EPCs, consistent with the notion that EPCs primarily promote angiogenesis through their paracrine functions [ 17 , 18 ]. Flt-1, KDR and TIE2 levels were also moderately reduced in DFO-induced senescent EPCs.…”
Section: Resultssupporting
confidence: 75%
“…Considering that DFO compromised the angiogenic activity of EPCs, we then examined whether four-day DFO treatment altered the expression of angiogenic proteins such as vascular endothelial growth factor (VEGF), Fms-related receptor tyrosine kinase 1 (Flt-1), kinase insert domain receptor (KDR) and TEK receptor tyrosine kinase (TIE2) in EPCs ( Figure 3C – 3F ). DFO strongly downregulated VEGF, the major angiogenic factor in EPCs, consistent with the notion that EPCs primarily promote angiogenesis through their paracrine functions [ 17 , 18 ]. Flt-1, KDR and TIE2 levels were also moderately reduced in DFO-induced senescent EPCs.…”
Section: Resultssupporting
confidence: 75%
“…More researchers showed that CD44, CD31 and vWF were all related to the differentiation of EPCs into endothelial cells 20–22 . Subsequently, we found that the expression of EPC‐related marker molecules CD44, CD31 and vWF decreased significantly after promoting the expression of EPC Kir2.1.…”
Section: Discussionmentioning
confidence: 79%
“…The functional association of identified miRNAs targeting specific mRNAs revealed that a series of miRNAs (hsa-mir-496, hsa-mir-151a, hsa-miR-296-3p, hsa-mir-148a, hsa-miR-365b-5p, hsa-miR-3687, hsa-mir-454, hsa-miR-155-5p, and hsa-miR-145-5p) differentially regulated the genes involved in cell adhesion, angiogenesis, cell cycle, JAK-STAT signaling, MAPK signaling, NO signaling, and VEGF signaling, finally favoring angiogenesis ( Kasiviswanathan et al, 2020 ). In a study on endothelial progenitor cells, cultured in simulated microgravity, a facilitation of functional angiogenic properties has been reported, with increased HIF-1α and eNOS/NO induced FAK/ERK1/2 pathway upregulation in HUVEC ( Kong et al, 2021 ).…”
Section: Physical-chemical Factors Controlling Wound Healingmentioning
confidence: 99%
“…However, their effectiveness in human patients remains to be established ( Jo et al, 2021 ; Mazini et al, 2021 ; Ullah et al, 2021 ). The proposal of proangiogenic paracrine secretion by stem and precursor cells cultured in microgravity has been provided ( Ratushnyy et al, 2018 ; Kong et al, 2021 ).…”
Section: Pharmacological Cellular and Physical Countermeasuresmentioning
confidence: 99%